2012
DOI: 10.1016/j.ijgo.2012.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal and Newborn Health Registry Study of the Global Network for Women's and Children's Health Research

Abstract: Objective To implement a vital statistics registry system to register pregnant women and document birth outcomes in the Global Network for Women’s and Children’s Health Research sites in Asia, Africa, and Latin America. Methods The Global Network sites began a prospective population-based pregnancy registry to identify all pregnant women and record pregnancy outcomes up to 42 days post-delivery in more than 100 defined low-resource geographic areas (clusters). Pregnant women were registered during pregnancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
178
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 14 publications
0
178
0
2
Order By: Relevance
“…The study was done in 106 communities at six sites in five low-income countries (Chimaltenango, Guatemala; Nagpur District and Karnataka District, India; Western Provence, Kenya; Thatta District, Pakistan; and Lusaka, Zambia) and at one site in a middle-income country (Corrientes, Argentina). 9 These seven sites were selected by the Eunice Kennedy Shriver National Institute of Child Health and Human Development in the United States of America (USA), which supports the Global Network for Women's and Children's Health Research, to represent rural or semi-urban geographical areas served by government health services. Each site included between six and 24 distinct communities.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study was done in 106 communities at six sites in five low-income countries (Chimaltenango, Guatemala; Nagpur District and Karnataka District, India; Western Provence, Kenya; Thatta District, Pakistan; and Lusaka, Zambia) and at one site in a middle-income country (Corrientes, Argentina). 9 These seven sites were selected by the Eunice Kennedy Shriver National Institute of Child Health and Human Development in the United States of America (USA), which supports the Global Network for Women's and Children's Health Research, to represent rural or semi-urban geographical areas served by government health services. Each site included between six and 24 distinct communities.…”
Section: Methodsmentioning
confidence: 99%
“…Details of this procedure have been described elsewhere. 9 Study data were entered onto Microsoft Access computer files (Microsoft, Redmond, USA) at each study site and data were edited before transmission to the central data centre at RTI International in the United States, where additional data edits were performed and the data were analysed using SAS version 9.2 (SAS Institute, Cary, USA). The study findings were reported using descriptive statistics and risk ratios were calculated for maternal, fetal and neonatal outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, other studies carried out in these communities between 2008 and 2011 may also have contributed to improved health outcomes. [28][29][30] Second, the number of HIV infections and deaths among HIVexposed children was relatively small. However, the use of statistical models to estimate the 24-month HIV-free survival rate in children increased the precision of our estimates.…”
Section: Discussionmentioning
confidence: 99%